Stereotypical Perception in Management: A Review and Expansion of Role Congruity Theory - del Carmen Triana, María; Song, Ruixiang; Um, Cyril Taewoong; Huang, Lei (Journal of Management, 2024)
Role congruity theory proposes that bias may arise from the perceived incongruity between stereotypes about a social group and expected requirements for success in a social role. Since its introduction, with a focus on gender roles and the development of prejudice against female leaders, management scholars have applied role congruity theory to understand the emergence and consequences of prejudice in a wide range of organizational settings. We provide a review of management research that has incorporated role congruity theory. In this review, we first identify the key constructs and predictions that underlie the theory. Then, we summarize the adoption of the theory in the management literature based on the effects of role incongruity on target evaluation, outcome, and adaptation. Lastly, we suggest potential areas for future development of the theory, including the expansion of the theory to include social roles beyond gender, the examination of multilevel and multidimensional role incongruity effects, and other relevant emerging topics. We hope that this review will promote the accessibility of role congruity theory to management researchers and stimulate the development and application of the theory in the field of management.